2018
DOI: 10.3390/jcm7120540
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Novel Cardiorenal Biomarkers in the Prediction and Early Detection of Congestive Kidney Injury Following Cardiac Surgery

Abstract: Acute Kidney Injury (AKI) in the context of right ventricular failure (RVF) is thought to be largely congestive in nature. This study assessed the utility of biomarkers high sensitivity cardiac troponin T (hs-cTnT), N-Terminal Pro-B-Type Natriuretic Peptide (NT-proBNP), and neutrophil gelatinase-associated lipocalin (NGAL) for prediction and early detection of congestive AKI (c-AKI) following cardiac surgery. This prospective nested case-control study recruited 350 consecutive patients undergoing elective card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 53 publications
(79 reference statements)
1
21
1
Order By: Relevance
“…Patients’ clinical characteristics, AKI susceptibility factors, 4 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 28 , 29 , 30 and renal nonrecovery factors for congestive heart failure or critical illness population 31 , 32 , 33 , 34 , 35 were identified according to previous studies or availability in our data set. The risk factors extracted included age, sex, underlying disease (i.e., diabetes mellitus, hypertension, CKD, liver cirrhosis, and malignancy), heart function assessment by New York Heart Association functional class, 36 and left ventricular ejection fraction.…”
Section: Methodsmentioning
confidence: 99%
“…Patients’ clinical characteristics, AKI susceptibility factors, 4 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 28 , 29 , 30 and renal nonrecovery factors for congestive heart failure or critical illness population 31 , 32 , 33 , 34 , 35 were identified according to previous studies or availability in our data set. The risk factors extracted included age, sex, underlying disease (i.e., diabetes mellitus, hypertension, CKD, liver cirrhosis, and malignancy), heart function assessment by New York Heart Association functional class, 36 and left ventricular ejection fraction.…”
Section: Methodsmentioning
confidence: 99%
“…Right ventricular failure in the perioperative setting is difficult to diagnose and even more challenging to treat. Refractory post‐operative RVF is associated with up to 22–90% likelihood of in‐hospital mortality, 2,9–11 as well as significant morbidity, including prolonged mechanical ventilation, intensive care unit (ICU) length of stay, renal and hepatic failure, and increased need for inotropic and mechanical circulatory support 7,12–14 . Despite its prognostic importance in cardiac surgery patients, no universally accepted definition of RVF exists in this setting 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Refractory post-operative RVF is associated with up to 22-90% likelihood of in-hospital mortality, 2,[9][10][11] as well as significant morbidity, including prolonged mechanical ventilation, intensive care unit (ICU) length of stay, renal and hepatic failure, and increased need for inotropic and mechanical circulatory support. 7,[12][13][14] Despite its prognostic importance in cardiac surgery patients, no universally accepted definition of RVF exists in this setting. 15 The lack of a standardized definition also prevents the incorporation of RVF in major cardiac surgery mortality risk models.…”
Section: Introductionmentioning
confidence: 99%
“…Serum N-terminal pro-B-type natriuretic peptide (NT-proBNP), as an inactive polypeptide of the pre-prohormone brain natriuretic peptide (BNP), is synthesized and released by cardiomyocytes in response to pressure and volume overload (9)(10)(11). Increasing evidence has shown that the NT-proBNP level is associated with AKI after cardiac surgery (12)(13)(14)(15), medical (non-surgical) patients in cardiac intensive care units (16), or unselected critically ill patients (17). Several studies have also validated NT-proBNP as a predictor of mortality in cardiac surgery patients (12,14,18,19).…”
Section: Introductionmentioning
confidence: 99%